Change Communication in Public Sectors: Practice of Yeka Sub-City Health Office, Addis Ababa, Ethiopia - Bushira, Eden (African Journal of Leadership and Development, 2020)
Internal communication has an important part to play in the effectiveness of change initiatives. This study explored Practices of Communication to Manage Change in two woredas health offices and health centers. Managers and employees were a target population to this study. The study sought to answer types of communication strategies and factors affecting the effectiveness of communication. A mixed approach was used for gathering the data required to answer the research questions. Survey was administered to 154 employees. Two focus groups discussions were undertaken with two woredas 16 board members of the health centers. Five managers from sub city and two woredas health offices were interviewed. The data gathered from these three methods were analyzed utilizing frequency distribution and also percentage for categorical variables. Qualitative data were grouped and interpreted. Analysis revealed that the major communication strategies including communicating objectives of the change, providing training about directives of the changes and introducing success of the change were employed successfully. However, lack of trust due to lack of answering for employee’s questions and introducing the effect of the change before the change took place were among the problems identified. A number of barriers to communication effectiveness including attitudinal problems and skill gap were identified. Managers within the offices should be more comprehensively briefed and trained about communication by integrating with change processes. In relation to this there must be a need to address the perceived gap between communication strategies with those employees who agreed or not perhaps initially through improved communication.